THE MAIN SOURCES OF ELECTRICITY PRODUCTION AND THEIR ANALYSIS IN THE CONDITIONS OF UZBEKISTAN - Toxirov , A.T; Sodiqova, F.J; Nasriddinov, D.Z (Innovative Development in Educational Activities, 2023)
The article examines the importance of energy in our daily lives, which is currently growing in demand, the analysis of 5 types of thermal energy generating stations ( NPP, TES, HPS, WPS and PPS), their impact on ecology and the country’s economy. Comparing the advantages and disadvantages of each station, conclusions and proposals were made about which of them is suitable for Uzbekistan.